2020
DOI: 10.1186/s13041-020-00613-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced complement of dopaminergic neurons in the substantia nigra pars compacta of mice with a constitutive “low footprint” genetic knockout of alpha-synuclein

Abstract: Previous studies of the alpha-synuclein null mutant mice on the C57Bl6 genetic background have revealed reduced number of dopaminergic neurons in their substantia nigra pars compacta (SNpc). However, the presence in genomes of the studied mouse lines of additional genetic modifications that affect expression of genes located in a close proximity to the alpha-synuclein-encoding Snca gene makes these data open to various interpretations. To unambiguously demonstrate that the absence of alpha-synuclein is the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…However, for production of the new parental line for this study (L5 line: Snca Δflox/Δflox + NSE/Cre-ERT2) a “low footprint” constituent knockout parental line B6(Cg)- Snca tm1.2Vlb /J (Ninkina et al 2015 ) was used instead of the knockout line originally described by Abeliovich et al ( 2000 ). This prevents any possible effects that might develop as the result of substantially increased level of expression of the Mmrn1 (Goloborshcheva et al 2020 ) and potentially, other genes located in close proximity to the Snca gene due to the presence of neo expression cassette in the modified Snca genomic locus of mice produced by Abeliovich and colleagues. The new parental line used here is yet to be deposited to The Jackson Laboratory but currently is available from authors by request.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for production of the new parental line for this study (L5 line: Snca Δflox/Δflox + NSE/Cre-ERT2) a “low footprint” constituent knockout parental line B6(Cg)- Snca tm1.2Vlb /J (Ninkina et al 2015 ) was used instead of the knockout line originally described by Abeliovich et al ( 2000 ). This prevents any possible effects that might develop as the result of substantially increased level of expression of the Mmrn1 (Goloborshcheva et al 2020 ) and potentially, other genes located in close proximity to the Snca gene due to the presence of neo expression cassette in the modified Snca genomic locus of mice produced by Abeliovich and colleagues. The new parental line used here is yet to be deposited to The Jackson Laboratory but currently is available from authors by request.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, conditional inactivation of the gene could create much-needed controls for many experiments studying propagation of alpha-synuclein pathology throughout the nervous system and testing anti-alphasynuclein aggregation drugs. Recently, we have produced a mouse line with the first coding exon of the Snca gene flanked by loxP sites and confirmed that Cre-recombination leads to complete inactivation of the gene-when such inactivation was triggered in the germ line of ''floxed'' mice it created a novel ''low footprint'' constituent knockout line (Ninkina et al 2015;Goloborshcheva et al 2020). Further studies demonstrated that 4 months after conditional panneuronal inactivation of the Snca gene by tamoxifeninduced Cre-ERT2-driven recombination in adult (6month old) or ageing (12-month old) mice alphasynuclein becomes virtually undetectable in the striatum (Ninkina et al 2020), suggesting that these mice could be successfully used for certain ageing studies.…”
Section: Introductionmentioning
confidence: 89%
“…One of five slides from each of eight series was stained with hematoxylin and eosin. Electrode positions in Pt and MC were visualised without additional immunostaining, whereas for those in SN and VTA, an adjacent slide was stained with antibodies against tyrosine hydroxylase (TH, mouse monoclonal antibody, clone TH-2, Sigma, diluted 1:1000) and secondary Goat anti-mouse IgG (H+L) highly cross-adsorbed second antibodies (Alexa Fluor 488, Thermo A11029 diluted 1:1000) as described previously [ 43 ]. The borders of SN and VTA on histological sections were outlined using the atlas of TH-positive cells distribution [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first and subsequent studies on the effects of MPTP toxicity in alpha-synuclein-deficient animals showed surprising results: acute and chronic neurotoxin administration protocols did not have the desired effect on the death of the DA neurons of the SNpc despite lower cell counts [ 105 , 106 , 107 , 108 ] ( Table 2 ). Moreover, several in vitro studies demonstrated that an overexpression of human alpha-synuclein was associated with enhanced cell death after MPP+ exposure [ 109 , 110 ].…”
Section: Parkinson’s Disease Is a Form Of Synucleinopathymentioning
confidence: 99%